Influence of Almond Supplementation on Recovery Responses to Unaccustomed Exercise in Untrained Adults. (14th June 2022) - Nieman, David; Arnett, Lathan; Arnold, Matthew; Blevins, Tondra; Casebolt, Shawn; Williams, Joshua
Abstract: Objectives: This study with untrained adults determined if 4-weeks supplementation with almonds compared to a matched calorie, common snack (cereal bars) had an influence on exercise performance, muscle soreness and damage, and mood states during a 4-d period after engaging in an acute, 90-min bout of eccentric exercise (90-EE). Methods: Participants included 64 healthy, non-obese male and female adults (30–65 years, BMI 23–30 kg/m 2 ) who were not engaged in regular resistance training. Participants were randomized to almond (57 g/d) (AL) and cereal bar (324 kcal/d) (CB) groups for 4 weeks prior to engaging in 90-EE (17 exercises). Changes in muscle soreness and damage biomarkers, exercise performance tests, and mood states were monitored before and after the 4-week supplementation period, immediately post-90-EE, and then each morning during a 4-d recovery period. Results: The 90-EE caused significant delayed onset of muscle soreness that peaked 1–2-d post-exercise with no group differences (time, p < 0.001, interaction, p = 0.187). Serum muscle damage biomarkers increased strongly in both groups but were significantly lower in AL vs. CB immediately post-90-EE (creatine kinase, p = 0.034, myoglobin, p = 0.036) and after 1-d recovery (creatine kinase, p = 0.013). Several measures of performance were negatively affected by 90-EE including the 60-yard shuttle run time, leg-back strength, bench press repetitions, and peak- and mean-power during the 30-sec Wingate test (all p < 0.01). AL vs. CB had higher levels of leg-back strength during recovery (interaction, p = 0.029), but the groups did not differ in other performance measures. Total mood disturbance (TMD) and fatigue increased post-90-EE, but the magnitude of these changes tended to be lower in AL vs. CB (interaction, p = 0.130, p = 0.051, respectively). Vigor was higher immediately post-90-EE in AL vs. CB (p = 0.060). Conclusions: The 90-EE protocol induced significant muscle damage, muscle soreness, reduced strength and power performance, and mood disturbance. AL vs. CB ingestion (4 weeks) was linked to reduced serum levels of muscle damage, higher levels of leg/back strength, and a lower magnitude of mood disturbance. Thus, chronic almond ingestion may help mitigate negative physiological and mental responses to unaccustomed exercise by untrained individuals. Funding Sources: Almond Board of California.